The Use of Authentic Environmental-Themed Texts in Reading Comprehension for High School Students: A Study on Ecoliteracy - Lubis, Bambang Nur Alamsyah; Mardiana, Rizdika; Sulistyaningrum, Siti Drivoka; Permana, Sudarya (English Teaching and Linguistics Journal (ETLiJ), 2026)
This study aimed to investigate the use of autentic environtmental-themed text in reading comprehension for high school student. The objective of the study focuse to investigate he use of authentic texts with environmental themes affect students' understanding of ecoliteracy values, to investigate the challenges do students and teachers face in using authentic texts with environmental themes in reading comprehension learning, to investigate students respond to reading comprehension learning using authentic texts with environmental themes, to investigate the use of authentic texts with environmental themes contribute to building ecological awareness in high school students. The A qualitative descriptive approach was chosen because this research aims to describe and analyze the phenomena, the source of the data was high schol students and the data was the result of classroom observations, interviews with teachers and students, and document analysis. By integrating these texts into language education, the research explores how they improve students' reading skills while instilling ecoliteracy values. The study highlights the significance of environmental issues, such as pollution, climate change, and resource sustainability, and how these texts connect students to real-world problems. The findings reveal that authentic texts foster critical thinking, social responsibility, and active participation in classroom discussions. However, challenges such as language complexity, access to quality texts, and students' ability to connect environmental issues to personal experiences were also identified. The study suggests that teacher training, improved access to resources, and real-world engagement can optimize the effectiveness of using authentic environmental-themed texts in education. This approach not only develops students' academic skills but also empowers them to become agents of change in promoting environmental sustainability.